Regulatory feedback cycle of the insulin-degrading enzyme and the amyloid precursor protein intracellular domain: Implications for Alzheimer’s disease - Lauer, Anna Andrea; Mett, Janine; Janitschke, Daniel; Thiel, Andrea; Stahlmann, Christoph P.; Bachmann, Cornel M.; Ritzmann, Felix; Schrul, Bianca; Müller, Ulrike C.; Stein, Reuven; Riemenschneider, Matthias; Grimm, Heike S.; et al. (Aging cell, 2020)
One of the major pathological hallmarks of Alzheimer´s disease (AD) is an accumulation of amyloid-β (Aβ) in brain tissue leading to formation of toxic oligomers and senile plaques. Under physiological conditions, a tightly balanced equilibrium between Aβ-production and -degradation is necessary to prevent pathological Aβ-accumulation. Here, we investigate the molecular mechanism how insulin-degrading enzyme (IDE), one of the major Aβ-degrading enzymes, is regulated and how amyloid precursor protein (APP) processing and Aβ-degradation is linked in a regulatory cycle to achieve this balance. In absence of Aβ-production caused by APP or Presenilin deficiency, IDE-mediated Aβ-degradation was decreased, accompanied by a decreased IDE activity, protein level, and expression. Similar results were obtained in cells only expressing a truncated APP, lacking the APP intracellular domain (AICD) suggesting that AICD promotes IDE expression. In return, APP overexpression mediated an increased IDE expression, comparable results were obtained with cells overexpressing C50, a truncated APP representing AICD. Beside these genetic approaches, also AICD peptide incubation and pharmacological inhibition of the γ-secretase preventing AICD production regulated IDE expression and promoter activity. By utilizing CRISPR/Cas9 APP and Presenilin knockout SH-SY5Y cells results were confirmed in a second cell line in addition to mouse embryonic fibroblasts. In vivo, IDE expression was decreased in mouse brains devoid of APP or AICD, which was in line with a significant correlation of APP expression level and IDE expression in human postmortem AD brains. Our results show a tight link between Aβ-production and Aβ-degradation forming a regulatory cycle in which AICD promotes Aβ-degradation via IDE and IDE itself limits its own production by degrading AICD.
Gesehen am 08.08.2024